Mathematical modeling of the crushed wood particles movement in pneumatic transport systems - Udovytskyi, O. M.; Baryliak, V. V. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
Pneumatic transport systems (PTS) are widely used in various branches of industries. The transportation of crushed material in such systems is carried out due to the air flow. In the woodworking industry, there are technological processes that are often accompanied by the formation of dust and other small air pollutants. Studying the movement of particles in polluted air makes it possible to transport or separate such particles, while spending less energy. The mathematical model of the movement of dusty air containing separate solid particles (production waste) was worked out, and based on it solution will allow separating and capturing crushed wood particles and reducing the cost of consumed electricity for transportation.